(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
For enterprise application development, cloud computing is going to new-fangled paradigm that meets the needs of today’s enterprises and helps them efficiently executing workflows in business and scientific applications. Workflow applications often require a very intricate runtime environment that is hard to create and maintain. Thus, cloud infrastructure is valued as an implementation platform for positioning technical workflows with features such as on-demand provisioning, scalability, reproducibility and resilience. To schedule multiple workflows in the cloud, we need to design the workflow before scheduling it. Therefore, in this paper we review the diverse work done by researchers for the workflow design as well as workflow scheduling.